Pragmatic Meaning and Manipulative Strategies in Uzbek and English Media Headlines - Bekberganova Khilola,; Bekberganov Avazbek,; Nazarboyev Azimboy, (INTEGRATION OF EDUCATION AND SCIENCE: GLOBAL CHALLENGES AND SOLUTIONS, 2026)
Media headlines play a crucial role in shaping readers’ perceptions by compressing complex information into short, attention-grabbing statements. This article examines the pragmatic meaning and manipulative strategies employed in Uzbek and English media headlines. Drawing on theories of pragmatics, including implicature, presupposition, speech acts, and evaluative language, the study explores how headlines influence readers’ interpretations and emotional responses. A qualitative comparative analysis of selected Uzbek and English online news headlines reveals both shared and culture-specific manipulative strategies, such as sensationalism, ambiguity, ideological framing, and emotional appeal. The findings demonstrate that while English media headlines often rely on implicit evaluation and irony, Uzbek headlines tend to employ presupposition and lexical intensification to guide interpretation. The study highlights the importance of pragmatic awareness for critical media literacy in a globalized information space.